CARBON ISOTOPES IN RIPHEAN CARBONATES FROM THE YENISEI RIDGE - Khabarov E.M.; Ponomarchuk V.A.; Morozova I.P.; Travin A.N. (My University, 1999)
Carbon isotope composition is determined in the Riphean (1450-1350 to 850-820 Ma) carbonate rocks from the Sukhoi Pit, Tungusik, and Oslyanka groups of the Yenisei Ridge eastern zones. The results of petrographic, geochemical, and isotopic studies show that limestone and dolomite are mainly devoid of signs of significant postsedimentation alteration and could preserve the C-isotope signature close to the initial value. Carbonate rocks from the basal (Korda Formation) and upper (Sosnovyi Formation) parts of the Sukhoi Pit Group are characterized by the C-isotope ratios close to zero. Overlying deposits younger than 1000 Ma span the long intervals of their sequence, where δ13C values are 2.5-4.5‰; with the extreems 5.6‰; these are separated by short intervals with lower δ13C values. The Dzhur rocks show the ascending trend of δ13C variations from 1.6-1.9 to 4.8‰ with the subsequent lowering of this parameter at the top of the formation. The Shuntarskaya Formation is characterized by positive δ13C values (1.9-3.2‰) in its lower part and by negative values (-2.8-5.0‰) in the upper part. In the Angara section of the Seryi Klyuch Formation, values of 3.0 to 4.4‰ prevail, lowering sometimes to 1.2-2.6‰. Carbonate subformations of the Dadykta (Kamenka zone) and Rybnaya (Gorbilok zone) formations yield uniform δ13C values (3.0-4.5‰) with their probable decrease at the top of the sections. The lower part of the Dashka Formation is marked by the ascending trend of δ13C variations from 0.3 to 5.0‰; higher, there are variations from 2.3-3.0 to 4.5-5.6‰. The comparison of the δ13C values characteristic of rocks from the Yenisei Ridge with those obtained for rocks from the Turukhansk uplift and Baikit arch shows that they are close in the first case and substantially differ in the second. δ13C values in carbonate rocks of the Yenisei Ridge (except the Korda rocks) generally coincide with those recorded in 1100-850-Ma-old carbonates from other regions. Nonetheless, rocks from the Dadykta and Dashka formations with high (4-5‰) positive δ13C values might be younger than 850 Ma.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей